A Scoping Review of Lean Six Sigma and Industry 4.0 Integration: Readiness Dimensions, Transformation Strategies, and Contextual Enablers in Manufacturing - Totok Kurniawan; Gatot Yudoko; Yuanita Handayati (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2026)
Research on Lean Six Sigma (LSS) and Industry 4.0 (I4.0) integration in manufacturing has grown rapidly, yet remains fragmented between operational excellence and digital transformation streams. Existing studies predominantly employ cross-sectional designs that treat variables in isolation, while current readiness frameworks such as IMPULS, SIRI, and INDI 4.0 offer diagnostic assessment without prescriptive transformation guidance. This scoping review synthesizes 63 peer-reviewed studies (2020–2026) from the Scopus database, following the Arksey and O'Malley framework and PRISMA-ScR guidelines. Three research questions guide the inquiry: (RQ1) what LSS variables influence I4.0 readiness, (RQ2) what transformation strategies are employed and what outcomes they produce, and (RQ3) under what contextual conditions does integration yield effective results and what gaps remain. The review identifies 10 LSS variables and 7 transformation strategy dimensions. Technology Integration, Top Management Commitment, and Process Standardization are the most frequently reported variables across the reviewed studies, consistent with accounts suggesting that digital technologies cannot compensate for operational instability. The reviewed studies collectively describe the LSS–I4.0 relationship as bidirectional, with LSS providing the process foundation for digitalization while I4.0 technologies are reported to reciprocally enhance lean effectiveness through real-time analytics and predictive capabilities. Leadership and Change Management, Human Capital Development, and Phased Roadmap are the most frequently reported strategic dimensions, suggesting that the literature increasingly frames transformation as an organizational challenge rather than a technology procurement exercise. However, these insights are drawn from a geographically and sectorally concentrated evidence base dominated by Indian manufacturing contexts, with Southeast Asian economies and process industries such as food and beverages remaining largely unexamined, and systems thinking methodologies that could capture holistic interdependencies notably absent. To address these limitations, a conceptual framework integrating LSS variables, transformation strategies, and contextual moderators within a feedback-driven system is proposed to guide future research in underexplored contexts.